Pressure determination in a T-shape micro-channel - Teo, Andrew Mou Chuan. (2012)
The main objective of this project is to investigate the pressure distribution in a micro-channel. To carry out the investigation, an experimental setup is designed to facilitate the pressure measurement and the visualization of the flow. The geometry used for the investigation is a T-shaped micro channel, with water flowing in the main channel and air in the perpendicular arm of the channel which is enclosed. In the experiment the pressure of interest is the pressure required to form a bubble at the T-junction. The bubble is formed by increasing the flow rate of the water. The bubble formation process is recorded for observation and measurement.